'Ragging': What the medical students of a health institute from Eastern Nepal say? - Shakya, DR; Maskey, R (Sunsari Technical College Journal, 2013)
Background: The view point of the students, the main stakeholder, regarding ragging bears a great significance on this tradition. Objective: To explore how medical students of a health science institute in eastern Nepal view ragging. Methodology: This is a semi-qualitative attitudinal study conducted in 2009/10 among medical students. An intensive questionnaire was prepared to assess different aspects of ragging. The questionnaire mainly focused on their view about ragging: positive and negative sides, their favour and some local issues, e.g. personal experience, common modes of ragging in the institute and their suggestions for the change. Some questions were open ended. Every 5th students of the frame of all medical students of B. P. Koirala Institute of health sciences (BPKIHS) were approached personally or through mail for response to the questionnaire. Hence, 200 were approached and we could collect 60 responses for analysis. Results: Among 60 participating medical students of different academic programs, 28.3% were female and 66.8% were male. Average student age was 23 years. Thirty two percents of the respondents were in favour of some sort of ragging though a great majority expressed that there was a need of some modification in its current pattern in the institute. Many felt that it might facilitate socialization and some better form of interactive program was a need. Sixty eight percent respondents found ragging to be stressful. Conclusion: Ragging exists in BPKIHS though a majority of medical students were against it. They opined for the modification in the current tradition of ragging. DOI: http://dx.doi.org/10.3126/stcj.v1i1.8658 Sunsari Technical College Journal Vol.1(1) 2012 27-32